EFFECT OF ZINC SUPPLEMENTATION ON PREGNANCY COMPLICATIONS AND ANTHROPOMETRIC MEASUREMENTS OF INFANTS AT BIRTH - N Aminisani (Babol University of Medical Sciences, 2006)
BACKGROUND & OBJECTIVE: Maternal zinc supplementation has been suggested as a potential intervention to reduce the incidence of low birth weight (LWB). The results of placebo-controlled trials are inconsistent. The aim of this study was to evaluate the effect of zinc supplementation on pregnancy complications and outcome. METHODS: We conducted a double-blind, placebo-controlled trial in which 196 women who were selected from health care centers in Ardabil between 16-20 wk of pregnancy. Then, they randomly were allocated to receive zinc supplementation (as 220mg zinc sulfate) or placebo. All information of baseline characteristics, follow up forms, pregnancy complications and anthropometric measurement of infants were collected by trained midwifes. FINDINGS: Seventeen of the 196 women were excluded from study. The incidence of low birth weight (<2500 gr) was different significantly after zinc supplementation in placebo group (p=0.01). Also birth weight was higher in zinc group than placebo group (p=0.03). No significant effect of treatment was observed on pregnancy complications. However, pregnancy induced hypertension and IUGR were observed only in placebo group. CONCLUSION: This study showed zinc supplementation during pregnancy improved birth weight and reduced low birth weight.